The social patterning of Covid-19 vaccine uptake in older adults: A register-based cross-sectional study in Sweden - Spetz, Malin; Lundberg, Lisa; Nwaru, Chioma; Li, Huiqi; Santosa, Ailiana; Leach, Susannah; Gisslén, Magnus; Hammar, Niklas; Rosvall, Maria; Nyberg, Fredrik (The Lancet regional health. Europe, 2022)
A broad vaccination coverage is crucial for preventing the spread of Covid-19 and reduce serious illness or death. The aim of this study was to examine social inequalities in Covid-19 vaccination uptake as of 17th May 2021 among Swedish adults aged ≥ 60 years. The study population comprised a general population cohort aged 60 years or older (n = 350,805), representative of the Swedish population. Data were collected through the nationwide linked multi-register observational study SCIFI-PEARL, and associations between sociodemographic determinants and Covid-19 vaccination uptake were analysed using logistic regression. Intersectional analyses of sociodemographic heterogeneity were performed by taking several overlapping social dimensions into account. Data availability extended to 17 May 2021. The overall vaccination coverage was 87·2% by 17th May 2021. Younger age, male sex, lower income, living alone, and being born outside Sweden, were all associated with a lower uptake of vaccination. The lowest Covid-19 vaccination uptake was seen in individuals born in low-or middle-income countries, of which only 60% had received vaccination, with an odds ratio (OR) of not being vaccinated of 6·05 (95% CI: 5·85–6·26) compared to individuals born in Sweden. These associations persisted after adjustments for possible confounding factors. The intersectional analyses showed even larger variations in vaccination in cross-classified sociodemographic subgroups (ranging from 44% to 97%) with marked differences in uptake of vaccination within sociodemographic groups. The uptake of Covid-19 vaccine during the spring of 2021 in Sweden varied substantially both between and within sociodemographic groups. The use of an intersectional approach, taking several overlapping social dimensions into account at the same time rather than only using one-dimensional measures, contributes to a better understanding of the complexity in the uptake of vaccination. SciLifeLab / Knut & Alice Wallenberg Foundation, Swedish Research Council, Swedish government ALF-agreement, FORMAS.